Analysing Sustainable Competitive Advantage : Strategically Managing Resource Allocations to Achieve Operational Competitiveness - Malek, Nurul Aida Abdul; Shahzad, Khuram; Takala, Josu; Bojnec, Stefan; Papler, Drago; Liu, Yang (Polish Association for Production Management, 2015)
In today’s dynamic business environment, a key challenge for all companies is to make adaptive adjustments to their manufacturing strategy. This study demonstrates the competitive priorities of manufacturing strategy in hydro-power case company to evaluate the level of sustainable competitive advantage and also to further analyze how business strategies are aligned with manufacturing strategies. This research is based on new holistic analytical evaluation of manufacturing strategy index, sense and respond, and sustainable competitive advantage models. These models help to describe, evaluate,and optimize resource allocation to meet the performance requirements in dynamic decision making. Furthermore, these models evaluate operational competitiveness for manufacturing strategies according to the multi-criteria priority. The results show that the adjustments of competitive priorities in manufacturing strategies by implementing the proposed holistic analytical models are helpful in strategically managing business operations. The discussion derives the most critical attributes in business operations while alignment of resource allocation with competitive priorities help to strategically focus those attributes. In conclusion, we argue that resource allocation and manufacturing strategies have become the most important capabilities in a business environment where companies focus to get a sustainable competitive advantage.
Keywords: sustainable competitive advantage; sustainable operations; competitive priorities; sense and respond; manufacturing strategy index; adaptive strategy; fi=Tuotantotalous|en=Industrial Management|